BAZ2A (TIP5) is involved in epigenetic alterations in prostate cancer and its overexpression predicts disease recurrence - Gu, Lei; Kuner, Ruprecht; Sültmann, Holger; Brors, Benedikt; Korbel, Jan Oliver; Plass, Christoph (Nature genetics, 2015)
Prostate cancer is driven by a combination of genetic and/or epigenetic alterations. Epigenetic alterations are frequently observed in all human cancers, yet how aberrant epigenetic signatures are established is poorly understood. Here we show that the gene encoding BAZ2A (TIP5), a factor previously implicated in epigenetic rRNA gene silencing, is overexpressed in prostate cancer and is paradoxically involved in maintaining prostate cancer cell growth, a feature specific to cancer cells. BAZ2A regulates numerous protein-coding genes and directly interacts with EZH2 to maintain epigenetic silencing at genes repressed in metastasis. BAZ2A overexpression is tightly associated with a molecular subtype displaying a CpG island methylator phenotype (CIMP). Finally, high BAZ2A levels serve as an independent predictor of biochemical recurrence in a cohort of 7,682 individuals with prostate cancer. This work identifies a new aberrant role for the epigenetic regulator BAZ2A, which can also serve as a useful marker for metastatic potential in prostate cancer.
Published online 8 December 2014
Im PDF sind 3 weitere Seiten "Online methods"
Gesehen am 21.01.2021